(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today, the use of surface-active substances in various fields is increasing significantly around the world. This article analyzes the use of surfactants in various fields of industrial production, agriculture and everyday life.